Stationary distributions of the R[X]/R/1 cross-correlated queue. Issue 17 (2nd September 2017) - Panda, Gopinath; Banik, A. D.; Chaudhry, M. L.
ABSTRACT: We consider an infinite buffer single server queue wherein batch interarrival and service times are correlated having a bivariate mixture of rational ( R ) distributions, where R denotes the class of distributions with rational Laplace–Stieltjes transform (LST), i.e., ratio of a polynomial of degree at most n to a polynomial of degree n . The LST of actual waiting time distribution has been obtained using Wiener–Hopf factorization of the characteristic equation. The virtual waiting time, idle period (actual and virtual) distributions, as well as inter-departure time distribution between two successive customers have been presented. We derive an approximate stationary queue-length distribution at different time epochs using the Markovian assumption of the service time distribution. We also derive the exact steady-state queue-length distribution at an arbitrary epoch using distributional form of Little's law. Finally, some numerical results have been presented in the form of tables and figures.